The Effect of Push, Pull, and Mooring Factors on Customers’ Switching Intention to Green Cosmetics - Asri Sekar Mawar Firdausi; Basu Swastha Dharmmesta (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Nowadays, consumption patterns concern consumers since they have negative impacts on environmental sustainability. Marketers have conducted some efforts to create eco-friendly products. This condition has caused research into green marketing to grow significantly. Various studies have been conducted to examine consumers' behavior intentions toward green products. However, the theory applied to explain the phenomenon still has the potential to be developed. Thus, in this study, the researchers examine the consumers' switching intention from conventional cosmetics to green cosmetics, by applying the migration theory and the push-pull-mooring framework. The push factors are explained by the dissatisfaction variable and the low-quality variable. The alternative attractiveness variable explains the pull factor. Meanwhile, the mooring factors are explained by variety-seeking and the unfavorable subjective norm variables. PLS-SEM is used to analyze 198 consumers of conventional cosmetics. The results indicate that the pull factor is the main factor that supports the consumers' switching intention to green cosmetics, and the second is the push factor. Furthermore, the mooring factors are proven to moderate the effect of the pull factor on consumers' switching intention. On the other hand, the mooring factors are not shown to moderate the influence of the push factors on the consumers' switching intention.